Ultrahigh-power supercapacitors based on highly conductive graphene nanosheet/nanometer-sized carbide-derived carbon frameworks. (25th April 2018) - Yan, Pengtao; Zhang, Xuesha; Hou, Meiling; Liu, Yanyan; Liu, Ting; Liu, Kang; Zhang, Ruijun
Abstract: In order to develop energy storage devices with high power performance, electrodes should hold well-defined pathways for efficient ionic and electronic transport. Herein, we demonstrate a highly conductive graphene nanosheet/nanometer-sized carbide-derived carbon framework (hcGNS/nCDC). In this architecture, nCDC possesses short transport paths for electrolyte ions, thus ensuring the rapid ions transportation. The excellent electrical conductivity of hcGNS can reduce the electrode internal resistance for the supercapacitor and thus endows the hcGNS/nCDC composite electrodes with excellent electronic transportation performance. Electrochemical measurements show that the cyclic voltammogram of hcGNS/nCDC can maintain a rectangular-like shape with the increase of the scan rate from 5 mV s −1 to 20 V s −1, and the specific capacitance retention is up to 51% even at a high scan rate of 20 V s −1, suggesting ultrahigh power performance, which, to the best of our knowledge, is among the best power performances reported so far for the carbon materials. Furthermore, the hcGNS/nCDC composite also shows an excellent cycling stability (no drop in its capacitance occurs even after 10000 cycles). This work demonstrates the advantage in the ultrahigh power performance for the framework having both short transport pathways for electrolyte ions and high electrical conductivity.